TASAWUF DAN RADIKALISME ATAS NAMA ISLAM (Suatu Alternatif Mencegah Radikalisme di Dunia Islam) - Setyawan, Agus (Dialogia: Jurnal Studi Islam dan Sosial, 2016)
Abstract: Violence in the name of Islam is increasingly worrying. Mass murder, kidnapping and terror have spread throughout the world, including Indonesia. One of factors that caused those conditions is human failure in modern era. They lose their vision and spirituality. They learned divinity and religious doctrines instantly. It means that they just leaned those doctrines on the surface. While, the inner meaning of thariqat and haqiqat, are never been touch. As a result, they lost the truth and closed by power lust, selfish and self-righteous. In hence, religion becomes creepy. Then to eliminate this radicalism is by studying Sufism greater in depth, in order to gain batiniah knowledge. Its knowledge leads to the center of truth. And it manifests into beautiful forms, full of harmony and brotherhood. As the result, peaceful is reached without violence in the name of Islam.